Loosely Coupled Systems - Desautels, Edward; Chow, V.; Schneider, M. (University of Wisconsin-Madison Department of Computer Sciences, 1973)
The National Science Foundation is supporting an investigation into the costs and benefits of coupling a small stand-alone timesharing system (such as TSS-8 or RSTS-11) to a large multiprogrammed system (such a s OS/370 or 1108 EXEC8). A system is being designed which will support local limited resource time-sharing, remote batch operations, on-line remote job entry, and line concentration, as well as allow the small system to act as an "intelligent." terminal. The system will allow the migration of programs and data between the two systems as well as allow the user of the small system to access all physical resources of the larger one. The system will be initally implemented on a Datacraft 6024/1108 pairing but a primary goal of the design is to generalize to other machine pairs. These loosely coupled systems will increase the practical modes of access to computing services and hardware resources.